PERAN ILMU BIOTAKSONOMISERANGGA DALAM PEMBANGUNAN PERTANIAN BERKELANJUTAN DI ERA GLOBALISASI - Sri Suharni Siwi (Research Center for Biology-Indonesian Institute of Sciences, 2006)
Diagnostic materials have been recently faced by more complexity species due to the evolution's accelerated in agro ecosystem.Biotaxonomy is needed for searching solutions technology of sustainable agriculture, and anticipating problems that may appeared during the agricultural development proses. Biotaxonomy is a tool for integrating biological aspects, beginning of inventory, description, cataloging, study of distribution and the perspective evolution. The contribution to applied sciences has often supplied the key to the solution of problems for IPM and biological control provided accurate identification of the exact country of origin of insect pests and their total fauna of parasites and predator. Since the establishment of the World Trade Organization in 1995, volume and intensity of trade in agricultural product increased tremendously. To prevent the entry or spread of a pest, rules based on health and safety ground had been set out internationally under the agreement on the Application of Sanitary and Phytosanitary Measures (the SPS Agreement). In the context of international trade, the exporting country obliged to provide a list of pests likely to be associated with the commodity to be able importing country to conduct pest risk analysis and establish phytosanitary regulations. In order to meet these obligations, however, the developing countries have not benefited as developed countries, due to unabilily to provide an adequate description of health status of agricultural industries and pest-records based on voucher specimens held in properly well curated collection. The extensive specimen-based pest record held in the reference insect collection Bogor is an asset national that can provide the most reliable evidence of the plant health status of the country that have been long time ago neglected. The collection can provide a country with a powerful tool to assist bids for market access and to justify measures to exclude potentially harmful exotic pests entering the country. Therefore, such insect collection should be security well managed, and database digitally for easily accesses. Sectors of interest should worked together to realize that hopes. Without such efforts, global policy market has just only more impoverish our farmers and the possibility our commodities products pursued internationally on the other hand our local markets felled with product commodities import as has been seen at this time.